2013
DOI: 10.1371/journal.pone.0070919
|View full text |Cite
|
Sign up to set email alerts
|

Programmatically Selected Multidrug-Resistant Strains Drive the Emergence of Extensively Drug-Resistant Tuberculosis in South Africa

Abstract: BackgroundSouth Africa shows one of the highest global burdens of multidrug-resistant (MDR) and extensively drug-resistant (XDR) tuberculosis (TB). Since 2002, MDR-TB in South Africa has been treated by a standardized combination therapy, which until 2010 included ofloxacin, kanamycin, ethionamide, ethambutol and pyrazinamide. Since 2010, ethambutol has been replaced by cycloserine or terizidone. The effect of standardized treatment on the acquisition of XDR-TB is not currently known.MethodsWe genetically char… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(39 citation statements)
references
References 37 publications
2
37
0
Order By: Relevance
“…The continued use of these two drugs, together with undetected ethionamide resistance, weakened the MDR treatment regimen culminating in the selection of XDR tuberculosis strains. 126,127 Clones of genetically distinct strains have now evolved to become the dominant circulating pre-XDR and XDR tuberculosis strains in defined geographical regions, as observed in eastern Europe, 82,85,104 Portugal, 67 South Africa, 48,95 and South America. 99 …”
Section: The Contribution Of Molecular Epidemiology To the History Ofmentioning
confidence: 99%
“…The continued use of these two drugs, together with undetected ethionamide resistance, weakened the MDR treatment regimen culminating in the selection of XDR tuberculosis strains. 126,127 Clones of genetically distinct strains have now evolved to become the dominant circulating pre-XDR and XDR tuberculosis strains in defined geographical regions, as observed in eastern Europe, 82,85,104 Portugal, 67 South Africa, 48,95 and South America. 99 …”
Section: The Contribution Of Molecular Epidemiology To the History Ofmentioning
confidence: 99%
“…It is worth noting that extrinsic factors such as the economic and social situation of individuals or populations, the major political events (e.g., the fall of the Soviet Union) and the quality of TB control programmes also strongly influence the speed of drug resistance spread (Eldholm et al., 2016; Klopper et al., 2013; Müller, Chihota, et al., 2013). In vivo, the drug resistance acquisition also greatly varies depending on the location of bacterial populations in the body and the characteristics of the drugs (Kempker et al., 2015; Warner et al., 2015).…”
Section: Mutation Rate and Drug Resistance Acquisitionmentioning
confidence: 99%
“…This hypothesis is supported by the lack of pnc A mutant clusters, thus reflecting a low transmission potential. However, clusters of pnc A mutants have been described in some specific MDR and XDR M. tuberculosis outbreaks in South Africa and in Argentina showing the successful transmission of these PZA‐resistant clones (Cohen et al., 2015; Eldholm et al., 2015; Müller, Chihota, et al., 2013). The development of experimental evolution studies will allow assessing the biological cost magnitude of pnc A mutations.…”
Section: Fitness Cost Of Drug Resistance‐associated Mutationsmentioning
confidence: 99%
“…The presence of an inhA mutation may also alert the clinician not to include ethionamide or prothionamide in the MDR-TB treatment regimen due to potential crossresistance to these agents with this genetic mechanism in the background (3,4). Recent studies of programmatic selection of ethionamide-resistant MDR-TB strains in South Africa in the absence of this information clearly underlines the importance of the clinical impact of this question (7). In addition, INH monoresistance can be quite high in certain populous and high-burden set-tings such as India, where the rate of INH monoresistance may reach 10% (8).…”
Section: Is Rapid Confirmation Of the Fact That The Patient Has Mdr-omentioning
confidence: 99%
“…When used in combination with RIF, PZA shortens the duration of treatment from 1 year to 6 months (3). Recent clinical investigations clarified that PZA resistance has become an underestimated problem, since it may occur in up to 43% of MDR-TB strains (7,17). Additional treatment outcome studies that aimed to address the clinical significance of in vitro PZA resistance have shown that a FQ-based MDR regimen increased early culture conversion and treatment completion by 38% versus a similar treatment without PZA (18,19).…”
Section: (Iii) Is There a Need For A Rapid Screening Test For Pyrazinmentioning
confidence: 99%